2012
DOI: 10.1007/s00266-012-9919-9
|View full text |Cite
|
Sign up to set email alerts
|

Should We Be Analysing Breast Reduction Specimens? A Systematic Analysis of Over 1,000 Consecutive Cases

Abstract: This journal requires that authors assign a level of evidence to each article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 36 publications
4
29
0
4
Order By: Relevance
“…In our study, the rate of AMBL in patients with no history of breast cancer was 3.3%. The previous studies that included only patients with no history of breast cancer reported the rate of AMBL to be between 1.5 and 14% 5,7–26 . The wide range of reported rates of AMBL in different studies can be attributed to different pathological assessment methods of RM specimens between institutions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, the rate of AMBL in patients with no history of breast cancer was 3.3%. The previous studies that included only patients with no history of breast cancer reported the rate of AMBL to be between 1.5 and 14% 5,7–26 . The wide range of reported rates of AMBL in different studies can be attributed to different pathological assessment methods of RM specimens between institutions.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that patients with a history of breast cancer have an increased risk of metachronous breast cancer 2–4 . In this context, previous studies that analysed RM specimens showed a higher rate of incidental breast cancer in patients with a history of breast cancer compared to patients with no history of breast cancer 5–11 . The rate of incidental atypical and malignant breast lesions (AMBL) in patients with no history of breast cancer ranged from 1.5 to 14% 5,7–26 .…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that routine histologic examination of the reduction mammaplasty specimens are not cost-effective since the incidence of occult carcinoma in reduction mammaplasty patients is low, and that histological analysis of specimens should be restricted to high-risk patients and those over 30 years of age [24,25]. However, these authors did not take the breast lesions with elevated cancer risks into account when they calculated the price of histologic examination of reduction mammaplasty specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are within the higher end of the range reported in previous studies (2-13), which in part may be explained due to inclusion of in situ carcinomas in our study. In some studies, for example, LCIS results are not included in the cancer findings (6). There has been a debate concerning the role of LCIS as a precursor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The highest incidences are from institutional studies (2,3), and the lowest are from large population-based studies (4,5). A literature review by Hassan and Pacifico (6), however, demonstrated variations in study methodologies, inclusion of in situ carcinomas, and what is defined as a relevant breast pathology finding. This discrepancy makes studies difficult to compare.…”
Section: Introductionmentioning
confidence: 99%